Genetics of Epilepsies with Focal Sharp Waves - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The clinical manifestations and genetic aspects in 147 children with benign focal sharp waves were evaluated at the Epilepsy Center, Raisdorf, Germany.